2014
DOI: 10.1007/s00394-014-0717-9
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate and green tea extracts protect against ER stress induced by a high-fat diet in skeletal muscle of mice

Abstract: Purpose We tested the hypothesis that polyphenol-rich extracts can reduce endoplasmic reticulum (ER) stress induced by a high-fat diet (HFD) in skeletal muscle of mice. Methods Mice were randomly assigned to four groups receiving during 20 weeks either a standard chow control (CTRL), or a HFD supplemented, or not, with pomegranate (HFD ? P) or green tea (HFD ? GT) extracts. After the nutritional intervention, mice were killed and gastrocnemius muscles were taken. Proteins and mRNA were measured by Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…Although the decrease of protein synthesis in tibialis anterior muscle of mice after TNF‐α injection did not reach the statistical threshold, there was a clear protective effect of PE feeding on protein synthesis, Akt/mTOR pathway, and protein degradation markers explaining the reduced muscle mass wasting. These findings are in good agreement with previous results showing that PE counteracts the increase of ubiquitin ligases mafbx and murf1 mRNA during a high‐fat diet . Moreover, incubation of C2C12 myotubes with urolithin A also reduced the activation of the ubiquitin‐proteasome pathway assessed by the mRNA level of murf1 and mafbx as well as the ubiquitinated proteins.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the decrease of protein synthesis in tibialis anterior muscle of mice after TNF‐α injection did not reach the statistical threshold, there was a clear protective effect of PE feeding on protein synthesis, Akt/mTOR pathway, and protein degradation markers explaining the reduced muscle mass wasting. These findings are in good agreement with previous results showing that PE counteracts the increase of ubiquitin ligases mafbx and murf1 mRNA during a high‐fat diet . Moreover, incubation of C2C12 myotubes with urolithin A also reduced the activation of the ubiquitin‐proteasome pathway assessed by the mRNA level of murf1 and mafbx as well as the ubiquitinated proteins.…”
Section: Discussionsupporting
confidence: 92%
“…We found that muscle mass were not lower in PE mice, compared to those observed in STD mice, suggesting that body fat rather than muscle mass could be reduced by PE supplementation. Others studies did not report any difference in body mass gain when PE was used in combination with a high-fat diet [9,31], but the punicalagins content of the extract was lower in these studies. Therefore, further studies are required to investigate a potential protective effect of higher doses of punicalagins on body fat storage, possibly due to changes in intestinal lipid absorption [9].…”
Section: Pe Protects Skeletal Muscle Against Tnf-␣-induced Muscle Wasmentioning
confidence: 56%
“…These antioxidant agents include natural antioxidants [e.g., vitamin C, E, coenzyme Q10, alpha-lipoic acid, fish oil containing n-3 fatty acids, betaine, and S-adenosyl-methionine (SAMe)], L-arginine, small-molecule metabolites (e.g., GSH-ethyl ester and NAC), and plants polyphenols (silimarin in milk thistle, curcumin, esculetin, sulforaphane, resveratrol, quercetin, epigallocatechin-3-gallate, caffeic acid phenethyl ester, and many others) (Andringa et al, 2010;Bailey et al, 2006;Cao et al, 2013;Cederbaum, 2010;Choi et al, 2013;Chung et al, 2012;Esfandiari et al, 2007;Ji & Kaplowitz, 2003;Kharbanda et al, 2012;Kim, Nagy, et al, 2014;Kim, Quon, & Kim, 2014;Lee, Mcgregor, et al, 2013;Lee, Yun, Seo, Kim, & Lee, 2014;Lieber, 2002;Marcolin et al, 2012;Nanji et al, 2003;Powell et al, 2010;Rodrigues et al, 2013;Scorletti et al, 2014;Shin et al, 2014;Song, et al, 2008;Surapaneni et al, 2014). These antioxidants, contained in many fruits and vegetables, show beneficial effects on AFLD, NAFLD, and DILI, although some of these antioxidants also exhibit significant protection in other tissues such as heart, muscle, and brain (Pallauf, Giller, Huebbe, & Rimbach, 2013;Rodriguez et al, 2015). Some of these agents include inhibitors of CYP2E1 such as diallyl sulfide in garlic, phenethyl isothiocyanate (Stice et al, 2015;Yoshigae, Sridar, Kent, & Hollenberg, 2013) in crucible vegetables, or dioscin in edible plants , although these inhibitors seem less potent than the synthetic CYP2E1 inhibitor CMZ (Hu et al, 1994) or YH439 ( Jeong et al, 1996).…”
Section: Translational Research Opportunitiesmentioning
confidence: 97%
“…[7][8][9][10] Supplementing the diet with ellagitannins attenuates muscle damage experienced during strenuous exercise, 11 and ellagitannin-rich pomegranate extract protects muscle against stresses induced by a high-fat diet. 12 Nevertheless, because of the low bioavailability of ellagitannins, 13 it is likely that ellagitannin-derived metabolites are responsible for the reported effects. Therefore, it seems important to characterize the effects of urolithins themselves.…”
Section: Introductionmentioning
confidence: 99%